La participación de los jóvenes en el entorno comunitario* (2019)
Young people participating in community spaces will understand the heterogeneity and diversity of forms and environments, from there, they construct their definition of participation. In the study conducted in various neighborhoods with young people from vulnerable sectors in Chile, contrary to what is assumed, we found high levels of youth participation. In this way, we can verify that young people find answers to their needs in local areas. Answers that they had lost due to disaffection and distance of conventional political and citizen participation.